A dynamic model for valuing flexible mining exploration projects under uncertainty. (June 2017) - Miranda, Oscar; Brandão, Luiz E.; Lazo Lazo, Juan
Abstract: Mining ventures are long term irreversible capital investments that operate in a highly uncertain environment and which typically present significant managerial flexibility. It is a well-known fact that due to their option-like characteristics, the value of these managerial flexibilities is not captured by traditional valuation techniques, such as the discounted cash flow method. In this article we develop a dynamic model for the assessment of the financial viability of flexible mining projects in the exploration stage (junior mines). We assume the firm has the option to defer the initial investment for a period of time, and once invested, has the additional flexibility to expand or even abandon the project. The model simulates the managerial decision making process and determines the value of the flexibility, or real options, associated with the mining project. On the other hand, for the case of firms that are listed in the stock market, the model assesses the likely impact of these options on the firm´s market value. We present a case study where we apply this model to a silver junior mining venture in Perú. The results indicate that the combined real options associated with the project may have a significant impact on its value, suggesting that the firm´s stock is undervalued by approximately 25%. Highlights: A dynamic model to assess financial viability of flexible junior mining projects. The model simulates the managerial decision making process in a mining project. The model determines the value of the project flexibilities (real options). The likely impact of these flexibilities on the firm´s market value is assessed. The model is applied to a silver junior mining project. The results suggest that the firm is undervalued by approximately 25%.